2007
DOI: 10.3842/sigma.2007.097
|View full text |Cite
|
Sign up to set email alerts
|

Differential Invariants of Conformal and Projective Surfaces

Abstract: Abstract. We show that, for both the conformal and projective groups, all the differential invariants of a generic surface in three-dimensional space can be written as combinations of the invariant derivatives of a single differential invariant. The proof is based on the equivariant method of moving frames.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Moreover, we prove that the algebra of surface differential invariants can, in fact, be generated by this single differential invariant, in the sense that all the higher order differential invariants can be obtained by repeatedly applying the two invariant differential operators associated with the moving frame to the generating invariant and taking functional combinations thereof. This is reminiscent of similar surprising recent results in Euclidean and equi-affine surface geometry, [12], as well as conformal and projective geometry, [7].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, we prove that the algebra of surface differential invariants can, in fact, be generated by this single differential invariant, in the sense that all the higher order differential invariants can be obtained by repeatedly applying the two invariant differential operators associated with the moving frame to the generating invariant and taking functional combinations thereof. This is reminiscent of similar surprising recent results in Euclidean and equi-affine surface geometry, [12], as well as conformal and projective geometry, [7].…”
Section: Introductionmentioning
confidence: 81%
“…We will eventually prove, using moving frame methods, the following result, which is very much in the spirit of those established in [12] and [7]. Theorem 4.1.…”
Section: Surfacesmentioning
confidence: 99%
“…For surfaces in 3-space, under the Euclidean and affine group, two curvatures with a syzygy describe the algebra of differential invariants. Using the tools presented here and their implementation, it was shown that the same is true for the projective and conformal group acting on surfaces [33]. Some cases of 3-dimensional submanifolds in 4-space were also given a computational treatment in [29,Section 7].…”
Section: Prospectsmentioning
confidence: 99%
“…Many simple examples, as well as computationally challenging ones, are treated in the papers [14,29,30] from which the material of this section is drawn as well as in, for instance, [33,49,39,42,40]. Here we wish to illustrate how the presented material is put into action on a well known example.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation